Reality as a Palimpsest: Information Disorder Practices in George Orwell’s 1984 and The Loudest Voice - Beatriz Valverde; Ana Valverde González (Anglica. An International Journal of English Studies)
Drawing upon mass communication theories, with special emphasis on Jean Baudrillard’s theory of simulacra and simulacrum, we will examine distortion of infor- mation practices in George Orwell’s 1984 (1949) and in the American TV miniseries The Loudest Voice (2019). Even though there is nearly a century between both works, socio-politically speaking, the control of information dissemination is equally important in both narrative products: in the maintaining of the status quo in an authoritarian system in 1984 and in the process of undermining the current US democratic system in The Loudest Voice. With this, we will argue that these literary and audiovisual texts are key for citizens to develop critical thinking skills and to question their worldviews, or, in Orwell’s own words, to exercise an uncommon common sense, which entails independence of thought and integrity of mind.